Análisis comparativo de tecnologías Front End Angular Js Vs React Js, en el modelo de procesos para el desarrollo de aplicaciones web. - Anchundia Medrano, Luis Ali (2022)
The objective of this project is to carry out a comparative analysis between these frameworks: AngularJS vs. ReactJ, with this comparison, allows the reader to know the features that AngularJS provides and that has led it to be one of the market leaders. It is a study that also includes the development of a practical case to show how this tool works. It is worth mentioning that there are tools that are oriented to develop small projects and others that are more scalable, optimal and have a focus on business applications. Carrying out projects with the help of a Framework can be due to several reasons, such as the fact that the Framework adapts to an established architecture, these tools constitute some Frameworks and/or libraries based on web components such as Angular JS and ReactJS. Some are currently based on JavaScript, they are used in the development of most web applications and new tools are always appearing that seek to lead the market. In addition, with the constant evolution of web technologies, ideas can be materialized that years ago would be unthinkable, because the resources to build them did not exist. To conclude this document about web development, more specifically in MVC client frameworks based on JavaScript, I can say that the growth that these technologies have had in the last decade has been very great, this is due to the great tools that they provide to the developer and therefore the great community that is generated around them.